Growing up tobacco free : preventing nicotine addiction in children and youths - Lynch, Barbara S.; Bonnie, Richard J. (National Academy Press, 1994)
A report from the Committee on Preventing Nicotine Addiction in Children and Youths, Division of Behavioral Sciences and Mental Disorders, the Institute of Medicine.